Laparoscope combined with ureteroscope in the treatment of bile duct stones and cholecystolithiasis in a child: a case report and literature review - Fu, Chang; Jin, Hengwei; Fang, Lijun; Xu, Hongji (Frontiers in Medicine, 2024)
Cholecystolithiasis combined with bile duct stones is more and more common in children, but the surgical treatment is still controversial. We report on a 3-year-old boy, who underwent laparoscope combined with ureteroscope for choledocholithiasis with cholecystolithiasis. This combination therapy offers the possibility to treat pediatric patients with cholecystolithiasis and bile duct stones in low-resource settings where ERCP experience and child-specific surgical instruments are not available. Additionally, a comprehensive review of previous studies was conducted, summarizing various treatment methods and operative approaches. The surgical treatment of children should be made according to the specific situation to maximize the success of the operation and reduce the risk.